Turning on the biradical state of tetracyano-perylene and quaterrylenequinodimethanes by incorporation of additional thiophene rings - Zeng, Zebing (2018)
Polycyclic hydrocarbon with a singlet biradical ground state has recently become a hot topic among various studies on π-conjugated systems and it is of importance to understand the fundamental structure–biradical character–physical properties relationship. In this work, we found that after incorporation of two additional thiophene rings into the closed-shell tetracyano-perylene (Per-CN) and quaterrylenequinodimethanes (QR-CN), the obtained new quinoidal compounds QDTP and QDTQ became a singlet biradical in the ground state due to the recovery of aromaticity of the thiophene rings in the biradical form and additional steric repulsion between the thiophene rings and the rylene unit. The ground state geometries and electronic structures of QDTP and QDTQ were systematically studied by variable-temperature nuclear magnetic resonance, electron spin resonance, superconducting quantum interference device measurements and FT Raman spectroscopy, assisted by density functional theory calculations. Both compounds were found to be a singlet biradical in the ground state with a small singlet–triplet energy gap and the biradical character was enlarged by elongation of the π-conjugation length. Strong one-photon absorption and large two-photon absorption cross-sections were observed for both compounds in the near-infrared region. Our studies demonstrated that a slight structural modification could significantly change the ground state and the electronic, optical and magnetic properties of a pro-aromatic π-conjugated system, and finally lead to new materials with unique properties.